Ginsenoside-Rg1 Rescues Stress-Induced Depression-Like Behaviors via Suppression of Oxidative Stress and Neural Inflammation in Rats. (23rd March 2020) - Li, Ye; Wang, Liyan; Wang, Peng; Fan, Cuiqin; Zhang, Ping; Shen, Jie; Yu, Shu Yan
Abstract : Depression is an inflammatory-related condition, with the progression in neuronal damage resulting in major depression disorder. Ginsenoside-Rg1, a sterol extract from the herb Panax ginseng, has been shown to exert neuroprotective effects upon neurodegeneration disorders. However, whether ginsenoside-Rg1 confers antidepressant-like effects on neuroinflammation as associated with depression, as well as the possible mechanism involved in these neuroprotective effects, is currently unclear. In the present report, we show that treatment with ginsenoside-Rg1 (40 mg/kg, i.p.) significantly ameliorated depressive-like behaviors as induced by chronic unpredictable mild stress (CUMS) in a rat model of depression. Moreover, these CUMS rats treated with ginsenoside-Rg1 showed reductions in the levels of the oxidative stress products and the activity in the antioxidant stress kinase. Furthermore, CUMS rats treated with ginsenoside-Rg1 showed ameliorated neuroinflammation and associated neuronal apoptosis along with a reduction in dendritic spine atrophy and display of depressive behaviors. Taken together, the results of this study suggest that ginsenoside-Rg1 produces antidepressant-like effects in CUMS-exposed rats; and one of the mechanisms for these antidepressant-like effects of ginsenoside-Rg1 appears to involve protection against oxidative stress and thus the neuronal deterioration resulting from inflammatory responses. These findings provide evidence for the therapeutic potential of ginsenoside-Rg1 in the treatment of stress-related depression.